## Given the domain (-2,-1, 0, 1, 2}, determine the range for each expression. Use a

table of values.

6. x-2y = 6

1. y = 3x + 2

2.x + y = 8

7.y = (2-1)

3. y = 5x – 1

4, y = 3×2

8.x=y-3

9. y = x2 – 4x – 3

10. y=(x-1(x+1)

5. y – 2012

Skip to content
# Given the domain (-2,-1, 0, 1, 2}, determine the range for each

##
Given the domain (-2,-1, 0, 1, 2}, determine the range for each expression. Use a

##

table of values.

6. x-2y = 6

1. y = 3x + 2

2.x + y = 8

7.y = (2-1)

3. y = 5x – 1

4, y = 3×2

8.x=y-3

9. y = x2 – 4x – 3

10. y=(x-1(x+1)

5. y – 2012